The Political Economy of Fiscal Policy and Economic Management in Oil Exporting Countries - Eifert, Benn; Gelb, Alan; Borje Tallroth, Nils (World Bank, Washington, DC, 2014)
Despite massive oil rent incomes since the early 1970s, the economic performance of oil-exporting countries-with notable exceptions-is poor. While there is extensive literature on the management of oil resources, analysis of the underlying political determinants of this poor performance is more sparse. Drawing on concepts from the comparative institutionalist tradition in political science, the authors develop a generalized typology of political states that is used in analyzing the political economy of fiscal and economic management in oil-exporting countries with widely differing political systems. In assessing performance, the authors focus on issues of long-term savings, economic stabilization, and efficient use of oil rents. The comparisons of country experiences suggest that countries with strong, mature, democratic traditions have advantages in managing oil rents well because of their ability to reach consensus, their educated and informed electorates, and a high level of transparency that facilitates clear decisions on how to use rents over a long horizon. Yet even these systems, ensuring cautious use of oil income is a continuing struggle. Traditional and modernizing autocracies have also demonstrated their ability to sustain long decision horizons and implement developmental policies. But resistance to transparency and the danger of oil-led spending and expenditure commitments becoming the major legitimizing force behind the state may pose risk to the long-term sustainability of their current development strategies. In contrast, little positive effect can be expected from the politically unstable, predatory autocracies, which typically have very short policy horizons and sometimes the characteristics of "roving bandit" regimes. Factional democracies, with weak political parties and highly personalized politics, present particular challenges because they lack a sufficiently effective political system to create a consensus among strong competing interests. Special attention will be needed to increase transparency and raise public awareness in these countries. And oil rent makes it more difficult to sustain a constituency in favor of sound, longer-run economic management because it weakens incentives for agents to support checks and balances that impinge on their individual plans to appropriate the rents. The country comparisons further demonstrate that technical solutions-such as the establishment of oil stabilization funds and budgetary reforms-to enhance transparency and efficiency in the use of oil rents will not work well unless constituencies can be developed in support of such measures.